On the Obituary of Scientific Knowledge Monopoly - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
The August 15th 2013 Shanghai Academic Rankings of World Universities (ARWU) should leave policy makers wondering about whether the impressive growth experienced by 'latecomers in the industry' has moved hand-in-hand with contribution to knowledge by means of scientific publications. Against this background, we model the obituary of scientific knowledge monopoly in 99 countries using 21 catch-up panels from 6 regions (South Asia, Europe & Central Asia, East Asia & the Pacific, Middle East & North Africa, Latin America & the Caribbean and, Sub-Saharan Africa). The findings broadly show that the obituary of scientific knowledge monopoly by developed countries is not in the near-horizon. Advanced nations that have mastered the dynamics of knowledge monopoly will continue to lead the course of knowledge economy. Justifications for the patterns and policy implications are discussed.
Keywords: F42; O10; O30; O38; O57; 330; Research & Development; Catch-up; Knowledge Economy